The Response of Microbiota Community to Streptococcus agalactiae Infection in Zebrafish Intestine - Zhang, Qi-Lin; Li, Hong-Wei; Wu, Wei; Zhang, Man; Guo, Jun; Deng, Xian-Yu; Wang, Feng; Lin, Lian-Bing (Frontiers in Microbiology, 2019)
Recently, Streptococcus agalactiae has become a major pathogen leading to Streptococcosis. To understand the physiological responses of zebrafish (Danio rerio) to S. agalactiae, the intestinal microbiota composition of the intestine (12 and 24 hours post-infection, hpi, respectively) in zebrafish infected with S. agalactiae were investigated. The intestinal bacterial composition was analyzed using PacBio high-throughput full-length 16S rRNA gene sequencing. The most predominant bacteria in the zebrafish intestine were the Fusobacteria phylum and Sphingomonas genus. S. agalactiae infection affected the composition of partially intestinal microbiota. At the species level, the relative abundance of the pathogenic intestinal bacteria Aeromonas veronii, S. agalactiae, and Clostridium tarantellae significantly increased after S. agalactiae infection (p < 0.05), while that of the beneficial intestinal bacteria Bacillus licheniformis, Comamonas koreensis, and Romboutsia ilealis significantly decreased (p < 0.05), showing that S. agalactiae infection aggravates the zebrafish disease through promoting abundance of other intestinal pathogenic bacteria. This study is the first PacBio analyses of the zebrafish intestinal microbiota community under pathogenic infection. Results suggest that the S. agalactiae infection alters the intestinal flora structure in zebrafish.